ANALYSIS OF STUDENT COMPETENCE IN WRITING SCIENTIFIC PAPERS BASED ON INFORMATION TECHNOLOGY (IT) - H. Muhammad M; Ishak; Fadhl Mohammed Awadh Gharamah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
Globally, this article is related to students' competence in writing articles. This article aims to describe the content of scientific works as the product of the writing learning process based on information technology (IT). A qualitative descriptive method is used to analyze the data, with its application adapted to the guidelines of the conceptual study and theory of the writing process, writing needs analysis for scientific works, and empirical studies on the current conditions of IT-based scientific writing learning. The data analysis techniques in this research involve data reduction, data presentation, and conclusion drawing. The research findings indicate that, in general, students are still categorized as not fully understanding information technology on one hand. However, the scientific works in the form of articles and theses were rated as "good" based on 10 indicators of scientific work assessment. Meanwhile, the use of Bahasa Indonesia in communicating arguments, ideas, and main issues was classified as effective, as the choice of words, sentence usage, and paragraph structure met the requirements for proper and correct language use.